A revised method with a temperature constraint for assimilating satellite-derived humidity in forecasting sea fog over the Yellow Sea - Gao, Xiaoyu; Gao, Shanhong; Li, Ziru; Wang, Yongming (Frontiers in Earth Science, 2023)
Numerical forecast of sea fog is very challenging work because of its high sensitivity to model initial conditions. For better depicting the humidity structure of the marine atmospheric boundary layer (MABL), Wang et al. (2014) assimilated satellite-derived humidity from sea fog at its initial stage over the Yellow Sea (W14 method), using an extended three-dimensional variational data assimilation (3DVAR) with the Weather Research and Forecasting model (WRF). This article proposes a revised version of the W14 method. The major ingredient of the revision is the inclusion of a temperature constraint into the satellite-derived humidity, not only for the missed fog area that the W14 method primarily considers, but also for the false fog area that is not handled in the W14 method. The numerical experiment results of 10 sea fog cases over the Yellow Sea show that the revised method can effectively alleviate the wet bias occasionally occurring in the W14 method, resulting in an improvement by about 15% for an equitable threat score of the simulated fog area. In addition, a detailed case study is conducted to illustrate the working mechanism of the revised method, including sensitivity experiments focusing on the roles of two kinds of background error covariances (CV5 and CV6) in the assimilation by the WRF-3DVAR. The results suggest that CV6 with multivariate cross-correlation is probably more beneficial to the revised method’s performance.